Pemanfaatan Gadget Sebagai Media Pelestarian Bahasa Daerah Bagi Anak Usia Dini - Lestari, Endang; Setyanto, Suroto Rosyd; Mahanani, Endah Normawati (STKIP PGRI Ponorogo Press, 2025)
The purpose of this study was to determine the use of gadgets as a medium for preserving local language for early childhood. This study uses a qualitative descriptive method with data collection techniques through observation, interviews and documentation. In the data collection process, researcher also reviewed relevant literature and references. This study was conducted in Balerejo Village, Kebonsari District, Madiun Regency, with 25 students as subjects. Based on the results of the study, there are three things that greatly influence the success of preserving regional languages using gadgets, namely; (1) parental culture to maintain traditional concepts in educating children; (2) the socio-economic status of parents from the lower middle class who tend to be stricter in raising children; and (3) parental education.